Dynamic Analysis of Engine Bearings - H. Hirani; K. Athre; S. Biswas (International Journal of Rotating Machinery)
This paper presents a simple methodology to evaluate the stiffness and damping coefficients of an engine bearing over a load cycle. A rapid technique is used to determine the shaft ‘limit cycle’ under engine dynamic loads. The proposed theoretical model is based on short and long bearing approximations. The results obtained by present approximation are compared with those obtained by numerical method. The influence of thermal effects on the stiffness and damping coefficients is predicted by using a simplified thermal analysis. In order to illustrate the application of the proposed scheme, one engine main bearing and a connecting rod bearing are analysed.